Aboriginal Street-involved Youth Experience Elevated Risk of Incarceration - Barker, Brittany (Public Health, 2015)
OBJECTIVES: Past research has identified risk factors associated with incarceration among adult Aboriginal populations; however, less is known about incarceration among street-involved Aboriginal youth. Therefore, we undertook this study to longitudinally investigate recent reports of incarceration among a prospective cohort of street-involved youth in Vancouver, Canada. STUDY DESIGN: Prospective cohort study. METHODS: Data were collected from a cohort of street-involved, drug-using youth from September 2005 to May 2013. Multivariate generalized estimating equation analyses were employed to examine the potential relationship between Aboriginal ancestry and recent incarceration. RESULTS: Among our sample of 1050 youth, 248 (24%) reported being of aboriginal ancestry, and 378 (36%) reported being incarcerated in the previous six months at some point during the study period. In multivariate analysis controlling for a range of potential confounders including drug use patterns and other risk factors, Aboriginal ancestry remained significantly associated with recent incarceration (adjusted odds ratio [AOR]=1.44; 95% confidence interval [CI]: 1.12–1.86). CONCLUSIONS: Even after adjusting for drug use patterns and other risk factors associated with incarceration, this study found that Aboriginal street-involved youth were still significantly more likely to be incarcerated than their non-Aboriginal peers. Given the established harms associated with incarceration these findings underscore the pressing need for systematic reform including culturally appropriate interventions to prevent Aboriginal youth from becoming involved with the criminal justice system.